AI as Person, Paradigm, and Structure: Notes toward an Ethics of AI - Scherz, Paul (Theological studies, 2024)
The unique capabilities of artificial intelligence (AI) have forced theologians to develop analytical categories beyond the instrumentalist model of technology. Recent work examines AI in terms of whether it has the qualities of a person, its effects on character, and its embedding in structures of sin. Constructive responses have focused on principles, communities, and virtues. None of these responses fully addresses concerns raised by critical analyses, suggesting that moral theology is still searching for a replacement for the instrumentalist model of technology.